The Contribution of Partial Meniscectomy to Preoperative Laxity and Laxity After Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction: In Vivo Kinematics With Navigation. Issue 13 (November 2019) - Grassi, Alberto; Di Paolo, Stefano; Lucidi, Gian Andrea; Macchiarola, Luca; Raggi, Federico; Zaffagnini, Stefano
Background: Limited in vivo kinematic information exists on the effect of clinical-based partial medial and lateral meniscectomy in the context of anterior cruciate ligament (ACL) reconstruction. Hypothesis: In patients with ACL deficiency, partial medial meniscus removal increases the anteroposterior (AP) laxity with compared with those with intact menisci, while partial lateral meniscus removal increases dynamic laxity. In addition, greater postoperative laxity would be identified in patients with partial medial meniscectomy. Study design: Cross-sectional study; Level of evidence, 3. Methods: A total of 164 patients with ACL tears were included in the present study and divided into 4 groups according to the meniscus treatment they underwent: patients with partial lateral meniscectomy (LM group), patients with partial medial meniscectomy (MM group), patients with partial medial and lateral meniscectomy (MLM group), and patients with intact menisci who did not undergo any meniscus treatment (IM group). A further division in 2 new homogeneous groups was made based on the surgical technique: 46 had an isolated single-bundle anatomic ACL reconstruction (ACL group), while 13 underwent a combined single-bundle anatomic ACL reconstruction and partial medial meniscectomy (MM-ACL group). Standard clinical laxities (AP translation at 30° of knee flexion, AP translation at 90° of knee flexion) and pivot-shift (PS) tests were quantified before and after surgery by means of a surgical navigation system dedicated to kinematic assessment. The PS test was quantified through 3 different parameters: the anterior displacement of the lateral tibial compartment (lateral AP); the posterior acceleration of the lateral AP during tibial reduction (posterior acceleration); and finally, the area included by the lateral AP translation with respect to the flexion/extension angle (area). Results: In the ACL-deficient status, the MM group showed a significantly greater tibial translation compared with the IM group ( P < .0001 for AP displacement at 30° [AP30] and 90° [AP90] of flexion) and the LM group ( P = .002 for AP30 and P < .0001 for AP90). In the PS test, the area of LM group was significantly larger (57%; P = .0175) than the one of the IM group. After ACL reconstruction, AP translation at 30° was restored, while the AP90 remained significantly greater at 1.3 mm ( P = .0262) in the MM-ACL group compared with those with intact menisci. Conclusion: Before ACL reconstruction, partial medial meniscectomy increased AP laxity at 30° and 90° and lateral meniscectomy increased dynamic PS laxity with respect to intact menisci. Anatomic single-bundle ACL reconstruction decreased laxities, but a residual anterior translation of 1.3 mm at 90° remained in patients with partial medial meniscectomy, with respect to those with intact menisci.